2018
DOI: 10.1016/j.tetlet.2018.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Total synthesis of pseudacyclins A–E by an on-resin head-to-side chain concomitant cyclization-cleavage reaction

Abstract: Taking advantage of the nucleophile-sensitive ester link of oxime resin, a novel synthetic strategy was applied to the first synthesis of a type of cyclic peptides known as pseudacyclins A-E. The endocyclic ornithine side-chain part was incorporated by an on-resin acid-catalyzed concomitant cyclization-cleavage reaction after a selective deprotection of orthogonally protected ornithine. The synthetic methodology gives high macrocyclization yields and low oligomerization sideproducts. The combination used of so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…An alternative methodology was also developed using entirely on-resin synthesis and biorthogonal protection in N -Boc-L-Thr(O t Bu)-OH [ 50 ]. In 2018, Bérubé et al reported the on-resin synthesis of pseudacyclins A–E via a similar head-to-side chain concomitant cyclization–cleavage strategy [ 51 ].…”
Section: Microwave-assisted And/or Solid-supported Synthesis Of Macro...mentioning
confidence: 99%
“…An alternative methodology was also developed using entirely on-resin synthesis and biorthogonal protection in N -Boc-L-Thr(O t Bu)-OH [ 50 ]. In 2018, Bérubé et al reported the on-resin synthesis of pseudacyclins A–E via a similar head-to-side chain concomitant cyclization–cleavage strategy [ 51 ].…”
Section: Microwave-assisted And/or Solid-supported Synthesis Of Macro...mentioning
confidence: 99%
“…Voyer and co‐workers have reported the solid‐phase synthesis of pseudacyclins A−E by using an oxime resin, which is removable by nucleophilic replacement (Scheme 24). [93] Based on this character of the oxime resin, Boc SPPS was appropriately chosen to synthesize these peptides. It began with anchoring ʟ‐Ile or ʟ‐Val ( 158 ) onto the oxime resin ( 159 ), followed by elongation of the peptide with Boc chemistry.…”
Section: Solid‐phase Total Synthesis Of Cyclic Peptidesmentioning
confidence: 99%